2006
DOI: 10.1038/sj.emboj.7601196
|View full text |Cite
|
Sign up to set email alerts
|

Rapid accessibility of nucleosomal DNA in yeast on a second time scale

Abstract: Packaging DNA in nucleosomes and higher-order chromatin structures restricts its accessibility and constitutes a barrier for all DNA transactions including gene regulation and DNA repair. How and how fast proteins find access to DNA buried in chromatin of living cells is poorly understood. To address this question in a real time in vivo approach, we investigated DNA repair by photolyase in yeast. We show that overexpressed photolyase, a lightdependent DNA-repair enzyme, recognizes and repairs UVdamaged DNA wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 69 publications
2
48
0
Order By: Relevance
“…The detachments involve only the ends of the nucleosome, i.e., basepairs of the SH-6.5 DNA segment and, in the nucleosome without the H3 tails, basepairs of the SH6.5 segment, whereas the segments located further in the nucleosome remain attached to the histone octamer. This result is in agreement with experimental studies on nucleosomal DNA unwrapping that suggest that nucleosomal DNA ends involving at least 20-30 bp are able to dissociate spontaneously from the protein core (4)(5)(6)(7)(8). An explanation for this behavior is that the last 13 basepairs on each side are tangential to the protein core and consequently form weaker contacts with the core than the other DNA segments that are bent around the histone octamer (47).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The detachments involve only the ends of the nucleosome, i.e., basepairs of the SH-6.5 DNA segment and, in the nucleosome without the H3 tails, basepairs of the SH6.5 segment, whereas the segments located further in the nucleosome remain attached to the histone octamer. This result is in agreement with experimental studies on nucleosomal DNA unwrapping that suggest that nucleosomal DNA ends involving at least 20-30 bp are able to dissociate spontaneously from the protein core (4)(5)(6)(7)(8). An explanation for this behavior is that the last 13 basepairs on each side are tangential to the protein core and consequently form weaker contacts with the core than the other DNA segments that are bent around the histone octamer (47).…”
Section: Discussionsupporting
confidence: 90%
“…Restriction enzyme accessibility assays of DNA target sites buried in the NCP suggest that the nucleosome possesses an intrinsic mechanism exposing its DNA (4). Further studies, including bulk and single molecule fluorescence energy transfer (FRET), have shown that the nucleosome exists in a dynamic equilibrium between a closed state, in which the DNA is fully wrapped, and open states in which the DNA is partially detached at the edges of the nucleosome (5)(6)(7)(8)(9). In agreement with these observations, cryo-electron microscopy studies show that the amount of DNA associated with the histone octamer and the entry/exit angle of the DNA are highly variable (10).…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies suggest that not only is site exposure an intrinsic property of nucleosomes in vitro, but it appears to be functionally important in vivo. A remarkable cooperative binding behavior predicted by the site exposure model occurs in vivo [1]; and studies on UV photodamage repair by photolyase in vivo suggest that the rate is too fast to be consistent with remodeling factor action and must instead reflect intrinsic nucleosome dynamics [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thoma and co-workers have shown that photolyase activity is greatly impaired in nucleosomes and is modulated by chromatin structure (29,30). Interestingly, in many organisms, including Saccharomyces cerevisiae, DNA photolyase repairs CPDs effectively on a time scale of seconds, implying the use of additional mechanisms for gaining access to CPDs in cells (31). Thus, compared with the stepwise repair of CPDs during NER, DNA photolyase provides a direct analysis of DNA accessibility in a positioned nucleosome in vitro.…”
mentioning
confidence: 99%